Erratum: "Antiphospholipid antibody syndrome as a cause of inferior vena cava thrombosis" (Turkish Journal of Pediatrics (2001) vol. 46 (2) (194-196)) - Tütüncüler, Filiz; Cihangiro?lu, M. Mutlu; Aydino?lu, A. Hakan; Aygün, A. Denizmen (My University, 2005)
[Abstract Not Available]
Keywords: erratum; error